Close Encounters Under the Muslim Ban: Mobile Media, Intimacy, and Augmented Whiteness - Wong, Danielle (Theatre Research in Canada / Recherches théâtrales au Canada)

(untitled) (Graduate Centre for the Study of Drama, University of Toronto, 2020)
This article examines how everyday mobile media produce discursive and affective modes of closeness that circulate as part of the Canada-US border-making process under the Muslim ban. I contend that although the #WelcomeToCanada hashtag, which was made popular by Justin Trudeau’s tweets in response to the US travel ban, presents an inclusive, multicultural Canada that appears to contrast the white supremacist, xenophobic narrative of Donald Trump’s executive order, its performance of flexible Canadian borders actually renders ubiquitous, and therefore augments, the default whiteness of the heteropatriarchal national body imagined by liberal narratives of inclusion. I compare #WelcomeToCanada to Sikh Canadian comedian Jus Reign’s Snapchat story about the Quebec City mosque attack and suggest that his overly faced selfies reveal the violence of a colourblind state gaze that functions like so-called neutral algorithmic vision. Jus Reign’s excessive closeness to his smartphone performs an ambivalent rupture of the universalizing vision on which neoliberal multiculturalism is based, emphasizing the racist logics of facial detection technology even as he characterizes Islamophobia as a particularly US discourse.